Deep sedation using intranasal dexmedetomidine followed by intravenous propofol for pediatric dental treatment - Yun Liu; Binghua Li; Xiaoran Wu; Bin Xia; Xudong Yang; Tong Cheng (BMC Oral Health)
Abstract Objective To evaluate the safety and efficacy of intranasal dexmedetomidine combined with propofol for pediatric dental sedation, and identify risk factors associated with major adverse events during deep sedation. Methods From June 2016 to August 2024, children who were unable to cooperate with the short-term oral treatment under non-pharmacological behavior or conscious sedation were selected for inclusion in the study. Intranasal dexmedetomidine 2 µg/kg was administered to facilitate preoperative sedation. Furthermore, a topical anesthetic, lidocaine gel, was applied to the venipuncture site. Once adequate sedation was achieved, venipuncture was performed. If preoperative sedation failed, sevoflurane inhalation was used to facilitate venipuncture. During the oral treatment, continuous target-controlled infusion (TCI) of propofol was administered to maintain a Bispectral index (BIS) of 50–70, ensuring deep sedation. Primary outcomes: Major adverse events (hypoxia, tachycardia, and bradycardia). Secondary outcomes: Less severe events (choking cough, gross body movement, and postoperative agitation) and risk factor exploration (interrelationships between tonsillar hypertrophy, surgery duration, and adverse events). Results A total of 513 children (359 boys, 69.98%; 154 girls, 30.02%) were enrolled in the study. Oral treatment was successfully completed in 100% of children. Surgery duration significantly influenced the incidence of major adverse events (p < 0.05), with a receiver operating characteristic (ROC) curve identifying 79 min as the optimal cutoff (AUC = 0.653, 95% CI: 0.573–0.733). Tonsillar hypertrophy was associated with a 4.6-fold increased risk of adverse events (OR = 4.61, 95% CI: 1.2–17.8; P = 0.017), driven by higher rates of hypoxemia (33.3% vs. 3.3%, P < 0.001) and choking cough (9.5% vs. 0%, P < 0.001). Conclusions This study establishes intranasal dexmedetomidine premedication followed by target-controlled propofol infusion sedation as a safe, effective alternative to general anesthesia for short-duration pediatric dental procedures (< 2 h).